Intervenção farmacêutica para pacientes com diabetes mellitus tipo 2 insulino-dependente em uma unidade básica de saúde do oeste do Paraná. - Silva, Daniela Marques da (2024)
According to the International Diabetes Federation (IDF), the global prevalence of DM is 8.8%, which means that there are 415 million people living with DM, and of these, half do not know they have the disease. DM is a set of metabolic disorders of multiple etiology, arising from an absolute insulin deficiency (Type 1 DM) or characterized by insulin resistance and/or reduced insulin secretion (Type 2 DM), which is the most prevalent, with approximately 90 to 95% of cases. Although various prescription medications can play a vital role in controlling symptoms and preventing complications, non-adherence to these therapies is highly prevalent and has been linked to increases in morbidity, mortality, and healthcare costs. Pharmaceutical Care is developed within the context of pharmaceutical care, which involves direct interaction between the pharmaceutical professional and the patient aimed at improving quality of life, executing it with ethics, skills and co-responsibilities in the prevention, recovery and promotion of health, integrated into a health team. The objective of CF is to improve the patient's quality of life through pharmacotherapy, seeking results that bring benefits to both the patient and the healthcare system. Adherence to medication is one of the key factors in the context of Rational Use of Medicines. To evaluate patient adherence regarding the use of recommended medications, pharmacotherapy, complications of the disease, number of missed insulin injections, patient knowledge regarding the script and the complexity of pharmacotherapy, the following tests were applied: Modified Morisky-Green (MGT ), Diabetes Complication (DC), Pharmacotherapy Complexity (CP), MedTake (MT) and Self-Compliance Test (ATC). 14 patients were evaluated, divided into adherent and non-adherent to pharmacotherapy. Through the application of the MGM questionnaire, 5 patients (35.71%) were considered adherent, while 9 patients (64.29%) were classified as non-adherent. Type 2 Diabetes Mellitus together with Arterial Hypertension are the main chronic diseases associated with the increase in polypharmacy or polypharmacy. During the pharmacotherapeutic monitoring of the studied population, nine types of DRPs were identified, related to necessity, effectiveness and safety, where of the 14 patients, all of them presented some problem related to the medication, a fact that favored the lack of control of blood pressure and blood glucose levels. When evaluating risk factors and concomitant diseases in a group of patients, it was observed that the vast majority, 93%, had a family history of cardiovascular disease, with only 7% not having this condition. Smoking was reported by 43% of patients, while the majority, 57%, did not have a smoking habit. Notably, a sedentary lifestyle was present in all patients, demonstrating an inactive lifestyle. Regarding weight, 79% of individuals were classified as being overweight or obese, and 21% had a weight within the range considered normal. In conclusion, throughout the study period, statistically significant decreasing trends were observed in the variables Systolic Blood Pressure, Diastolic Blood Pressure, Fasting Glycemia, Glycated Hemoglobin (HbA1c), Total Cholesterol, Triglycerides and LDL, contrasting with a significant trend of increase in HDL (High Density Cholesterol). All patients were reevaluated after interventions. After this analysis, it was found that 83.3% of patients showed an improvement in their general health conditions associated with the use of medications. What may have contributed to the improvement, in addition to the adequacy of pharmacotherapy, were the guidelines and frequency of visits to resolve doubts and monitor the treatment. The patient feels confident in clarifying their doubts and feels engaged in their treatment, thus improving laboratory parameters and consequently their quality of life.